2010
DOI: 10.5465/amj.2010.48037420
|View full text |Cite
|
Sign up to set email alerts
|

Activating Cross-Boundary Knowledge: The Role of Simmelian Ties in the Generation of Innovations

Abstract: In this article, we study the conditions under which having ties that span organizational boundaries (bridging ties) are conducive to the generation of innovations. Whereas previous research has shown that bridging ties have a positive impact on innovative performance, our analysis of 276 R&D scientists and engineers reveals that there are no advantages associated with bridging per se. In contrast, our findings suggest that the advantages traditionally associated with bridging ties are contingent upon the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
434
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 511 publications
(461 citation statements)
references
References 46 publications
21
434
0
6
Order By: Relevance
“…Thus, it was not possible to identify whether people were apt to reach out to particular boundary-spanning ties-for example Simmelian ties (Tortoriello and Krackhardt 2010)-or how structural and relational factors might have jointly shaped interaction choices (Reagans and McEvily 2003). Access to a broader data set-for example an entire division or business unit-would allow for more nuanced, structural extensions of the theory developed in this paper.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Thus, it was not possible to identify whether people were apt to reach out to particular boundary-spanning ties-for example Simmelian ties (Tortoriello and Krackhardt 2010)-or how structural and relational factors might have jointly shaped interaction choices (Reagans and McEvily 2003). Access to a broader data set-for example an entire division or business unit-would allow for more nuanced, structural extensions of the theory developed in this paper.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…This implies that certain prestigious offices and celebrity actors have a disproportionate ability to build reputations. Again, our evidence is limited to a single large qualitative study, but future contributions may examine the literature on celebrity firms and celebrity CEOs (see Hayward et al, 2004;Wade et al, 2006;Rindova et al, 2006;Pfarrer et al, 2010), as well as cross-boundary knowledge flows (Tortoriello and Krackhardt, 2010). At issue here is when, how and why corporate reputations influence labour mobility as a way of quantifying the intangible 'value' associated with reputational benefits.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…A common knowledge (the intersection of individual knowledge assets) is required for the performance of operations and for joint problem solving. Mutual understanding is also important because it affects the organisational members' ability to evaluate, understand, and use the transferred knowledge (Tortoriello and Krackhardt, 2010). Brusoni and Prencipe showed that the amount of common knowledge required for effective knowledge integration is a key issue in aero engines research and other complex production systems ).…”
Section: A Knowledge-based View Of the Extending Enterprisementioning
confidence: 99%